The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1272/jnms.jnms.2020_87-303
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Immunoglobulin Attenuates Cecum Ligation and Puncture-Induced Acute Lung Injury by Inhibiting Apoptosis of Alveolar Epithelial Cells

Abstract: Intravenous immunoglobulin attenuates cecum ligation and puncture-induced acute lung injury by inhibiting apoptosis of alveolar epithelial cells IVIG improves survival of septic mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…14 Animal experiments have shown that IVIG could decrease the proinflammatory cytokines' concentrations in septic mice. 19 Data from animal inflammation models and human cells showed that IVIG could enhance the regulatory T-cell proliferation and suppress pro-inflammatory Th17 cells, 20,21 with decreased pro-inflammatory cytokines (such as IL-17A and IL-6) and increased anti-inflammatory cytokines (such as IL-10). 22,23 We also found that, after IVIG treatment, the IL-6 concentration in plasma was decreased in the COVID-19 patients (data were not shown), suggesting that the benefits by IVIG might be associated with reduced inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Animal experiments have shown that IVIG could decrease the proinflammatory cytokines' concentrations in septic mice. 19 Data from animal inflammation models and human cells showed that IVIG could enhance the regulatory T-cell proliferation and suppress pro-inflammatory Th17 cells, 20,21 with decreased pro-inflammatory cytokines (such as IL-17A and IL-6) and increased anti-inflammatory cytokines (such as IL-10). 22,23 We also found that, after IVIG treatment, the IL-6 concentration in plasma was decreased in the COVID-19 patients (data were not shown), suggesting that the benefits by IVIG might be associated with reduced inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Immunoglobulin has been used in the treatment of viral infectious diseases, such as viral pneumonia, and autoimmune diseases 14 . Animal experiments have shown that IVIG could decrease the pro‐inflammatory cytokines’ concentrations in septic mice 19 . Data from animal inflammation models and human cells showed that IVIG could enhance the regulatory T‐cell proliferation and suppress pro‐inflammatory Th17 cells, 20,21 with decreased pro‐inflammatory cytokines (such as IL‐17A and IL‐6) and increased anti‐inflammatory cytokines (such as IL‐10) 22,23 .…”
Section: Discussionmentioning
confidence: 99%
“…The cecum, usually located in the right upper abdomen, was extracted using anatomical forceps. A 3–0 silk suture was passed through the mesocecum, and the cecum was ligated at its upper third adjacent to its root [ 7 ]. The cecum was then bilaterally punctured by inserting an 18-gauge needle through the cecal wall followed by cecal pressing with sterile cotton swabs and extrusion of the intestinal contents through the punctured openings.…”
Section: Methodsmentioning
confidence: 99%
“…The rationale is the ability of the immunoglobulins to (i) recognize and neutralize pathogens and associated toxins, (ii) anti-apoptotic effect on immune cells, and (iii) inhibit transcription [ 43 ]. Although the application of IVIg has been found to significantly reduce the sequential organ failure assessment scores (SOFA), apoptosis [ 44 ], and disseminated intravascular coagulation (DIC) [ 45 ] while increasing the blood level of immunoglobulins [ 46 ], it was unable to reduce mortality in sepsis patients [ 47 ]. The meta-analysis carried out by Cui and his group in 2019 revealed reduced mortality among adult patients with sepsis by intravenous administration of IgM-enriched immunoglobulin (IVIgGM).…”
Section: Current Therapeutic Approaches To Treat Sepsismentioning
confidence: 99%